2003
DOI: 10.1017/s0022112003005615
|View full text |Cite
|
Sign up to set email alerts
|

Intermodal energy transfers in a proper orthogonal decomposition–Galerkin representation of a turbulent separated flow

Abstract: Energy transfers between modes obtained from the proper orthogonal decomposition (POD) of a turbulent flow past a backward-facing step are analysed with the aim of providing guidelines for modelling unresolved modes in truncated POD–Galerkin models. It is observed that energy transfers are local in the POD basis, and that the Fourier-decomposition-based concepts of forward and backward energy cascades are also valid in the POD basis, the net effect being a forward energy cascade. General features of the eddy-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
101
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(104 citation statements)
references
References 18 publications
3
101
0
Order By: Relevance
“…Since we consider a number of simultaneous coherent fluctuations, a new, suitable form of these equations is derived and further applied to the analysis of the gathered data. This approach is similar to an intermodal energy flow study presented by Couplet et al [14] (an energy exchange between a number of POD modes is considered therein) or, more recently, by Hosseini et al [15] (an energy exchange between a slowly-varying base flow; the first and the second harmonic of a wall-mounted pyramid's shedding are studied).…”
mentioning
confidence: 87%
“…Since we consider a number of simultaneous coherent fluctuations, a new, suitable form of these equations is derived and further applied to the analysis of the gathered data. This approach is similar to an intermodal energy flow study presented by Couplet et al [14] (an energy exchange between a number of POD modes is considered therein) or, more recently, by Hosseini et al [15] (an energy exchange between a slowly-varying base flow; the first and the second harmonic of a wall-mounted pyramid's shedding are studied).…”
mentioning
confidence: 87%
“…In the ROM literature, a common explanation for this failure of standard ROMs is the violation of the concept of energy cascade [3,8,9,14,18,19]. Indeed, in [20] it was shown that the concept of energy cascade is also valid in a POD setting: The main role of the neglected POD modes is to drain energy from the ROM. Thus, since standard ROMs fail to account for this transfer of energy from resolved to unresolved POD modes, they generally yield inaccurate results.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these models are similar to the large eddy simulation (LES) closure models. Indeed, to model the effect of the neglected POD modes, some authors start with the filtered equations and propose closure models for ROMs, just as in LES (see, e.g., [3,8,20]). Other authors, however, do not employ filtering and the LES analogy to develop models for the neglected POD modes (see, e.g., [9,[17][18][19]).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations